2023
DOI: 10.52131/pjhss.2023.1101.0346
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Service Quality and Innovation in Developing Customer Loyalty; The mediating role of Customer Commitment and Satisfaction

Abstract: The study's objectives were to investigate the nexus of service quality and innovation in developing customer loyalty, with customer commitment and satisfaction as mediating. To address this issue, a quantitative investigation was carried out by a researcher in Pakistan. The primary study material was assembled through a survey questionnaire, with a sample population of approximately 369 individuals, which included Pakistani citizens who made online purchases. SEM (Hypotheses testing) showed a strong positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Employees can demonstrate it while selection is based on their green behaviour intentions. This self-efficacy results from green recruitment that leads the employee to use it creatively and innovatively toward environmental sustainability (Singh et al, 2019;Khan et al 2023;Shahzad et al, 2021) So, to enhance their abilities, organizations are using training activities that result in green entrepreneurial abilities and generate more innovative ideas to address environmental problems. Motivation to learn new ways of environmental sustainability will ultimately improve employees' green habits, behavioural intentions, commitments, and attitudes.…”
Section: Pro-eb (Environmental Behaviour)mentioning
confidence: 99%
“…Employees can demonstrate it while selection is based on their green behaviour intentions. This self-efficacy results from green recruitment that leads the employee to use it creatively and innovatively toward environmental sustainability (Singh et al, 2019;Khan et al 2023;Shahzad et al, 2021) So, to enhance their abilities, organizations are using training activities that result in green entrepreneurial abilities and generate more innovative ideas to address environmental problems. Motivation to learn new ways of environmental sustainability will ultimately improve employees' green habits, behavioural intentions, commitments, and attitudes.…”
Section: Pro-eb (Environmental Behaviour)mentioning
confidence: 99%
“…This factor is relevant to interactional justice, particularly to consumer complaint behavior. New research suggests that this is related to the marketing context, and it is also found that it is a fair treatment that contributes to satisfaction with service encounters and enhanced evaluations of service to better overall evaluations of complaint handling and more favorable repurchase intentions (Sheikh & Khursheed, 2016;Khan et al, 2023).…”
Section: Interactional Justicementioning
confidence: 99%
“…Justice has also been found to be the best relationship between citizens and employees. The volunteer tax reduction system is a massive burden for individuals, which is not easy to bear (Alaaraj, Mohamed, & Bustamam, 2018;Khan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Companies may attain sustainability by better using their human resources. Hiring a human resource manager is a crucial component of a business's sustainability strategy since human resource management affects how an organization interacts with the outside world, which affects ecology and civilization (Saifulina N. et al, 2020;Sibt & Asim, 2023). According to Dumont, J. et al (2017), green HRM has been emphasized as a crucial component that influences employee green management practices and workers' economic sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%